Arquitetura no Feminino: a produção das arquitetas cearenses pioneiras no setor público - Peixoto, Ingrid Teixeira (2023)
This work investigates the invisibility of female production in the historiography of architecture and, by recognizing a biographical imbalance, the result of patriarchal structures, seeks to rescue the performance and presence of female architects discredited by history. The work stands out primarily for revealing a historical panorama where some timelines begin to be traced and for highlighting the role of women in the development of what was called in this work Architecture of Housing, Architecture of Symbol and Architecture of Power. Therefore, it intends to demonstrate the contributions of female architects in the Brazilian context, mainly aimed at the scenario of institutionally produced architecture in Ceará. Through the visibility of public architecture, produced between 1970-2000 and promoted by architects from Ceará, the aim is to reinforce the female presence in the design of the urban fabric, marking women's access to the so-called Architecture of Power. For this study, 3 professionals were selected, marked by important trajectories in the public sector: Maria Clara Nogueira Paes, Aída Montenegro and Nélia Romero. The work has a feminist epistemology and seeks not only to identify a relevant production, but to contribute to the historiography of Ceará regarding the topic, demonstrating the importance of making this rescue. The 3 pioneers, graduates of the School of Architecture at the Federal University of Ceará, fill gaps in the Ceará panorama related to the profession and, by documenting the production of these architects, this research adds to the work of recording local architecture, which has already been developed in research within the scope of the UFC Postgraduate Program in Architecture, Urbanism and Design. The research aims, therefore, to contribute to a greater balance in the scenario of architectural production in Ceará, contemplating public buildings produced by women and understanding how architects shaped the city's spaces, built architectures of housing, symbol and power and thus became , part of urban memory.